Evaluating the Effectiveness of the Tahfīẓ Al-Qur'an Program at Pondok Pesantren An-Nur Yogyakarta/ Evaluasi Efektivitas Program Taḥfīẓ Al-Qur’an di Pondok Pesantren An-Nur Yogyakarta - Sukiman; Fikriansyah (Edulab : Majalah Ilmiah Laboratorium Pendidikan, 2021)
This study aims to evaluate the effectiveness of the Taḥfīẓ al-Qur'an Program at An Nur Islamic Boarding School in Yogyakarta. This study uses qualitative evaluation research. The evaluation uses the CIPP model (context, input, process, product). The subjects of this study were caregivers, managers of the Taḥfīẓ al-Qur'an program, educators, and boarding students. The technique of determining the research sample using the purposive sampling technique. Data collection methods using interviews, observation, and documentation. Data analysis uses three steps, namely data reduction, data display, concluding/verification. Test the validity of the data using source and technique triangulation. This study indicates that the three aspects of the Taḥfīẓ al-Qur'an Program at An-Nur Islamic Boarding School, namely context, input, process, are very effective and one aspect, namely product, is an effective category. In general, it can be concluded that the Taḥfīẓ al-Qur'an Program at An-Nur Islamic Boarding School was carried out very effectively. The program has succeeded in creating al-Qur'an memorizers of good quality, responsibility, and akhlāq al-karīmah. Abstrak Tujuan penelitian ini adalah mengevaluasi efektivitas Program Taḥfīẓ al-Qur’an di Pondok Pesantren An Nur Yogyakarta. Penelitian ini menggunakan penelitian evaluasi kualitatif. Evaluasi menggunakan model CIPP (context, input, process, product). Subyek penelitian ini adalah pengasuh, pengelola program Taḥfīẓ al-Qur’an, pendidik dan para santri pondok. Teknik penentuan sampel penelitian menggunakan teknik purposive sampling. Metode pengumpulan data menggunakan wawancara, observasi, dan dokumentasi. Analisis data menggunakan tiga langkah, yaitu reduksi data, penyajian data, penarikan kesimpulan/verifikasi. Uji keabsahan data menggunakan triangulasi sumber dan teknik. Hasil penelitian menunjukkan bahwa tiga aspek Program Taḥfīẓ al-Qur’an di Pondok Pesantren An-Nur yakni konteks, input, proses termasuk kategori sangat efektif dan satu aspek, yakni produk termasuk kategori efektif. Secara umum dapat disimpulkan bahwa Program Taḥfīẓ al-Qur’an di Pondok Pesantren An-Nur dilaksanakan dengan sangat efektif. Program tersebut telah berhasil menciptakan penghafal al-Qur’an dengan kualitas yang baik, bertanggung jawab, dan berakhlak karimah.